Argyrodite‐Type Cu8GeSe6–xTex (0 ≤ x ≤ 2): Temperature‐Dependent Crystal Structure and Thermoelectric Properties. Issue 24 (12th November 2018) - Schwarzmüller, Stefan; Souchay, Daniel; Günther, Daniel; Gocke, Alex; Dovgaliuk, Iurii; Miller, Samuel A.; Snyder, G. Jeffrey; Oeckler, Oliver
Abstract : Substitution of Se by Te in argyrodite‐like Cu8 GeSe6 leads to compounds Cu8 GeSe6– x Te x (0 ≤ x ≤ 2) and involves a structure change from the Cu8 GeSe6 type to the Ag8 GeTe6 type. The crystal structure of Cu8 GeSe4.25 Te1.75 between 50 °C and 500 °C reveals pronounced disorder of Cu atoms that is best described by anharmonic atomic displacement parameters using the Gram‐Charlier expansion. Diffusion pathways are visualized by isosurfaces of joint probability density functions. The lattice parameter a increases with temperature in two linear regimes from 10.4682(18) Å to 10.609(3) Å with a superionic transition at 400 °C. The potential barrier for Cu is about 90 meV at 50 °C, which is in the range of typical ion conductors. Cu8 GeSe4 Te2 exhibits a higher thermoelectric figure of merit ( zT = 0.65 at 350 °C) than Cu8 GeSe6 ( zT = 0.2 at 350 °C). The application of an effective mass model reveals that the charge carrier concentration of 6 × 10 20 cm –3 is close to optimum. In addition, argyrodite‐type precipitates form heterostructures with a Cu‐ and Se‐doped matrix of germanium antimony tellurides in the quinary system Cu/Ge/Sb/Se/Te, whose transport properties were characterized. Abstract :